The lost impact from SFAS 142 - Ribeiro, Humberto (2013)
A substantial amount of current accounting literature is focused on goodwill write-offs. This interest was enhanced following the FASB’s effectiveness of the new business combinations accounting rules, which shifted the discussion from pooling of interests method elimination to the accounting treatment of purchased goodwill and other intangible assets. SFAS 142 replaced amortisation of acquired goodwill and other intangible assets with indefinite useful lives by impairment tests, keeping amortisation, under certain conditions, only for goodwill and intangible assets with finite useful lives. By doing so, the FASB added volatility to financial reporting, as assumed in SFAS 142 body text. Most literature is concerned with the reliability of impairment tests under SFAS 142, in the scope of the increasing use of fair value accounting, and in face of the “big bath” earnings management. However, literature seems to have been forgotten that nonamortisation of purchased goodwill and certain intangible assets has benefited earnings per share of firms that did not record impairment loss following SFAS 142 adoption. In this paper, SFAS 142 effects on M&A activity and on financial reporting are examined. Overall, no significant impacts of SFAS 142 on M&A activity were found. However, a significant positive effect of nonamortisation of goodwill on diluted EPS has been found. This positive effect was overshadowed by the so-called “big bath” earnings management, and is not documented in existing literature. Therefore this paper’ findings provide a novel contribute to enhance the understanding of earnings management under goodwill impairment accounting.